The lateral compartmentation of the yeast plasma membrane - Malinsky, Jan; Opekarová, Miroslava; Tanner, Widmar (Yeast (Chichester, England), 2010)
The plasma membrane of Saccharomyces cerevisiae contains large microdomains enriched in ergosterol, which house at least nine integral proteins, including proton symporters. The domains adopt a characteristic structure of furrow-like invaginations typically seen in freeze-fracture pictures of fungal cells. Being stable for the time comparable with the cell cycle duration, they might be considered as fixed islands (rafts) in an otherwise fluid yeast plasma membrane. Rapidly moving endocytic marker proteins avoid the microdomains; the domain-accumulated proton symporters consequently show a reduced rate of substrate-induced endocytosis and turnover.
Keywords: biologické modely; buněčná membrána; Models, Biological; Saccharomyces cerevisiae; Microscopy, Confocal; Saccharomyces cerevisiae Proteins; membránové mikrodomény; Saccharomyces cerevisiae - proteiny; Amino Acid Transport Systems, Basic; transportní systémy pro bazické aminokyseliny; Membrane Microdomains; konfokální mikroskopie; Cell Membrane